2021
DOI: 10.1108/ijoes-11-2020-0181
|View full text |Cite
|
Sign up to set email alerts
|

Do creditors value corporate social responsibility disclosure? Evidence from Ghana

Abstract: Purpose Drawing on risk mitigation theory, this study aims to examine the link between corporate social responsibility (CSR) disclosure and the cost of debt financing (CDF). In particular, this paper seeks to determine whether firms with higher CSR disclosure scores have a lower CDF. Design/methodology/approach This paper uses a panel data analysis of non-financial Ghanaian firms listed on the Ghana Stock Exchange from 2006 to 2019. The CSR index constructed from firms’ annual reports and sustainability repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
(142 reference statements)
1
6
0
Order By: Relevance
“…However, now CSR_AWARDS is positive and significant (α= 0.006, p < 0.10), which implies that, when a company wins an award, the cost of debt increases, because the market may believe that the PLCs overinvested in CSR activities to gain legitimacy (Barnea and Rubin 2010). The results of our study seem to be consistent with Boachie and Tetteh (2021) in Ghana, who found that lenders tend not to rely on CSR disclosures as a mitigating risk factor. The main concern by lenders is the possibility of overinvestment by management in CSR investments by diverting scarce resources (Barnea and Rubin 2010).…”
Section: Estimation Resultssupporting
confidence: 83%
“…However, now CSR_AWARDS is positive and significant (α= 0.006, p < 0.10), which implies that, when a company wins an award, the cost of debt increases, because the market may believe that the PLCs overinvested in CSR activities to gain legitimacy (Barnea and Rubin 2010). The results of our study seem to be consistent with Boachie and Tetteh (2021) in Ghana, who found that lenders tend not to rely on CSR disclosures as a mitigating risk factor. The main concern by lenders is the possibility of overinvestment by management in CSR investments by diverting scarce resources (Barnea and Rubin 2010).…”
Section: Estimation Resultssupporting
confidence: 83%
“…This is a quantitative measure that indicates the degree of transparency and scope in reporting ESG data. For the COD, we follow Francis et al (2005) by calculating it as the percentage of the interest expense in year t divided by the average interest‐bearing debt during year t (Boachie & Tetteh, 2021; Yeh et al, 2020). For the COE, we use the CAPM model of Sharfman and Fernando (2008), which considers the expected return on equity as an indicator of the cost of capital.…”
Section: Methodsmentioning
confidence: 99%
“…MTB measures the market valuation of the company relative to book value. Companies with high MTB could be expected to have lower financing costs to the extent that they present additional value over book value, which implies lower financial risk (Bhuiyan & Nguyen, 2019; Boachie & Tetteh, 2021; Erragragui, 2018; Hasan et al, 2017). ROA measures are included because default risk is lower for profitable firms and could reduce borrowing costs and the required rate of return (Arena, 2018; Boachie & Tetteh, 2021; Erragragui, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of CSR involved the creation of a CSR reporting index. To formulate this index, initial references were made to the items and checklists utilized in prior research covering specific themes (Boachie & Tetteh, 2021;Barauskaite & Streimikiene, 2021). The CSR disclosure items were extracted from the annual reports of companies.…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%